Segurança alimentar e nutricional nas crianças e adolescentes internados em hospitais vinculados ao SUS em Belo Horizonte - Filomena Camilo do Vale (2009)
Introduction : There are in Brazil specific law to the practice nutrition therapy on the interned patient. However the hospital malnutrition index is disturbing. At many hospitals still there is not a organized and in function the multiprofessional team (EM TN) . There are only few studies identifying hospitals and its team work. Objectives: To identify the efficiency of the EMTN on the nutritional development on children and teenagers and the malnutrition prevalence in this group, interned at hospitals related to SUS, in Belo Horizonte, from June to October of2008. Trace the demographic profile, laboratory- clinic and dietary of the sample and to evaluate the existence and function of EMTN at the macro local hospital of Minas Gerais. Method: Interned anthropometric and release of interned patients data with and absence of EMTN wasobtained. To evaluate the nutritional status through IMC and to evaluate the loss and gain of weight, as a way to evaluate the EMTN performance. From the records information was obtained to build the profile of the patients and to investigate the existence or not of local macro referencehospitals of Minas Gerais, it was sent questionnaires with questions of multiple choice and free composing questions to be answered by the hospital responsible staff. Results: In any researched hospital where the research was made, the fully execution of the 272/98 and RDC-63 low, which regulate the EMTN functioning. From the 289 children and teenagers ( 1 month to 14 years old ) participants of this study, it was found 7,9% and 10% of malnutrition, respectively on the hospital internment and release. The weight loss on the 289 evaluated samples was 172 (59,52%). The clinic diagnose was common related to acute respiratory disease. Cow milk was recommended to 20% of the youngs ( less than one year old). From 38 local hospitals 20 were included on the analyses and all informed to be adapted to EMTN. Conclusion: The malnutrition prevalence was 7,9% on the internment and 10% on the release. It was not possible to show in a clear way the distribution of EMTN on the development of the nutritional situation, however theloss of weight occurred on 59,5% of the patients, which suggest lack of performance of EMTN. The acute respiratory disease was most prevalent and there was indication of the EMTN presence in almost evaluated units. However, a new study is needed, through new method to assure theresults.